Human Rights Enforcement: Providing Social Security as a Standard for Labor Equity in Pekalongan Regency - Khasna, Syarifa; Aufan, Aries (Asian Journal of Law and Humanity, 2024)
The constitutional rights of workers' social security are basic rights obtained by workers in a company, these rights must be accepted by workers as regulated in the Law. This research aims to analyze the fulfillment of the constitutional social security rights of workers in Pekalongan Regency. This research is empirical juridical research with a statutory approach. Collection techniques are carried out through observation, interviews and documentation. The type of approach used is qualitative. The results show the fact that the government has not been optimal in carrying out or providing sanctions against companies that do not register their employees as BPJS social security participants. The Pekalongan Regency government's efforts to fulfill the constitutional rights of social security for workers include steps such as visiting existing companies to carry out outreach and participate in monitoring with BPJS Employment regarding BPJS Employment participation, but in its implementation the Government has not implemented it.